Comparisons between the Role of Working Mothers and Housewives in the Development of Children Aged 3-5 th Years - dian, lia; Dwi Arini, Muafiqoh; Musonah, Ngidoti; Meidya Pratiwi, Arantika (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
In the first 5 years of children life, the brains develop connections faster. The age of 3-5 years is also known as the golden age of children, where in this period children experience accelerated development in aspects of gross motor, fine motor, language and social independence. At an early age, children need appropriate care to achieve their optimal development. The mother's role is identical to the main caregiver in the family, one of which is a very important role for golden age period.  This study aims to determine the comparisons in the role of working mothers and housewives in the development of children aged 3-5th years in the Gamping Ist public health center working area  This is a cross-sectional study with a convenience sampling to recruit participants with a sample size of 100 respondents. The inclusion criteria in this study were toddlers aged 3-5 years, mothers aged 23-35 years, and toddlers who were still active in posyandu activity. Bivariate analysis uses The T-test. Based on the result, role of mother's housewives showed better child development. This is shown by the majority of results being appropriate or normal for this group of children. While the role of working mothers showed no significat difference with child development . There are differences in the roles of working mothers and housewives. Research shows that housewives have children with better overall development